Notch3 Knockout Suppresses Mouse Mammary Gland Development and Inhibits the Proliferation of 4T1 Murine Mammary Carcinoma Cells via CCL2/CCR4 Axis - Xiong, Wei; Tan, Junyu; Guo, Yuxian; Chen, Shuzhao; Fan, Liping; Li, Yaochen (Frontiers in Cell and Developmental Biology, 2020)
Our previous study found that Notch3 knockout mice exhibit defects in mammary gland development. To elucidate the underlying mechanism, tissue samples were subjected to RNA-seq, GO, and KEGG enrichment analyses and qRT-PCR validation. Of enriched pathways, chemokine signaling pathway and cytokine–cytokine receptor interaction were noticed in both Notch3wt/wt/Notch3wt/– and Notch3wt/wt/Notch3–/– mice, in which the expression of chemokine ligand 2 (CCL2) was sharply reduced in Notch3wt/– and Notch3–/– mammary gland tissues. The Mouse ENCODE transcriptome data reveal that the mammary gland fat pad exhibits a high CCL2, CCR2, and CCR4 expression, indicating that these molecules play important roles during mammary gland development. Specifically, defective mammary glands in Notch3 knockout mice could be partially rescued by CCL2 overexpression lentivirus through intraductal injection. An in vitro study showed that CCL2 overexpression promoted the proliferation, migration, and cancerous acinar formation of 4T1 cells, which could rescue the defective migration of 4T1 cells caused by Notch3 knockdown. We also found that Notch3 transcriptionally regulated the expression of CCL2 in a classical pattern. Our findings illustrated that Notch3-regulating CCL2/CCR4 axis should be an important signaling pathway for mammary gland development and should be a candidate target for breast cancer therapy.